AKTIVITAS ANTIMIKROBA EKSTRAK DAUN TEH HIJAU (Camellia sinensis) DAN JATI BELANDA (Guazuma ulmifolia Lamk.)TERHADAP MIKROBA PATOGEN SECARA BIOAUTOGRAPHY-TLC - Herwin Herwin; St. Maryam (Fakultas Farmasi UMI, 2017)
An investigation has been conducted on the antimicrobial activities of extract teh hijau leaves (Camellia sinensis) and jati belanda leaves (Guazuma ulmifolia Lamk.) using TLC-Bioautography. The aom of this research is to test the antimicrobial activity of extract against some pathogen microbes. The preliminary research conducted screening test using several tipe of microbes including Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysentriae, Staphylococcus aureus, Staphylococcus epidermidis, Strepthococcus mutans, and Vibrio cholera. The screening results of extract inhibited almost all of pathogen microbies, except Bacillus subtilis and Staphylococcus aureus for extract teh hijau leaves and Vibrio cholera, Staphylococcus aureus, and Escherichia coli for extract jati belanda leaves. The research was continued with the antimicrobial activity against severeral microbes at different Rf and the result showed that the higher inhibited at Staphylococcus epidermidis Rf 0,02 and Shigella dysentriae Rf 0,49, 0,73 and 0,8 for teh hijau leaves, Pseudomonas aeruginosa Rf 0,02 dan 0,49 for jati belanda leaves. That extracts have antimicrobial activity to several pathogen microbes, so that are can use as one of alternative antimicrobial.